Analisis Tuturan Ritual Ngalap Semangat Suku Tidung Di Sebuku Ditinjau Dari Bentuk Mantra - Mulyati, Mulyati; Arifin, Syaiful; Indrahastuti, Tri (Adjektiva: Educational Languages and Literature Studies, 2021)
This study discusses the form of the mantra in the ritual speech of the Ngalap Spirit of the Tidung Tribe in Sebuku. Mantra is a word or speech that contains wisdom and supernatural powers. The power of the spell is thought to be able to heal or bring harm. This research is focused on analyzing the form of the mantra in the speech of the Ngalap Spirit Ritual of the Tidung tribe as one of the oral literatures that needs to be developed and preserved because it contains high literary values. The research was conducted with the aim of describing the form of the mantra and the ritual tradition of ngalap the spirit of the Tidung tribe in Sebuku. The method used in this research is a field research method with a qualitative approach that is described descriptively. Data collection techniques used in this study were interview techniques, note-taking techniques and recording techniques. The data analysis technique used is a qualitative descriptive analysis technique. The results of the research obtained are (1) the form of the mantra: a. The form of the line in the first mantra consists of 5 lines, each line contains 2-6 words and consists of 3-10 syllables; b. The form of the first mantra stanza, that is, each stanza consists of 5 lines and contains 2-6 words; c. The choice of words used in the traditional mantra ngalap, the spirit of the Tidung tribe does not only use the Tidung language but also uses the Indonesian language. It's just that the Tidung language is more dominant in its use in the traditional speech of ngalap, the spirit of the Tidung tribe.